2019
DOI: 10.1016/j.scriptamat.2018.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Basal slip of ⟨a⟩ screw dislocations in hexagonal titanium

Abstract: Basal slip of a screw dislocations in hexagonal closed-packed titanium is investigated with ab initio calculations. We show that a basal dissociation is highly unstable and reconfigures to other structures dissociated in a first order pyramidal plane. The obtained mechanism for basal slip corresponds to the migration of the partial dislocations and of the associated stacking fault ribbon in a direction perpendicular to the dissociation plane. Presented results indicate that both basal and pyramidal slip will o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…E inter SF−X is the interaction energy of the stacking fault with the solute atom. Its calculations is described in Appendix C. Using for the core radius r c = a √ 3/2 ∼ 2.55Å, the same value as in our previous study [29], one obtains the results shown as solid lines in Fig. 4.…”
Section: Energy Variationmentioning
confidence: 67%
See 2 more Smart Citations
“…E inter SF−X is the interaction energy of the stacking fault with the solute atom. Its calculations is described in Appendix C. Using for the core radius r c = a √ 3/2 ∼ 2.55Å, the same value as in our previous study [29], one obtains the results shown as solid lines in Fig. 4.…”
Section: Energy Variationmentioning
confidence: 67%
“…Above room temperatures, where the friction associated with this locking-unlocking glide mechanism becomes negligible, the lattice friction originates from the interaction of interstitial solute elements, in particular oxygen which is inevitably present in titanium alloys, with the core of the screw dislocations [17,19,28]. As for secondary slip systems, ab initio calculations have shown that a screw dislocations gliding in pyramidal or basal planes need to overcome a high energy barrier [27,29], thus leading to a mobility controlled by the nucleation and propagation of kink pairs in both cases [21,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basal slip appears also easier than pyramidal slip in titanium, with screw dislocations gliding through a slow and viscous motion compatible with a Peierls mechanism [7]. As ab initio calculations have shown that a a screw dislocation dissociated in a basal plane is unstable in titanium [37], basal glide in titanium is also realized without any basal dissociation. The same mechanism, where the screw dislocation glides in a basal planes trough the nucleation and propagation of kink-pairs while remaining dissociated in another plane, either prismatic or pyramidal, is therefore expected in titanium.…”
Section: Discussionmentioning
confidence: 97%
“…[36] Perhaps non-intuitively for those familiar with slip in fcc metals, there is no stable core dissociation in basal planes of Ti, and as a consequence, glide in the basal plane has all the features of a Peierls mechanism where screw orientation can be locked by dissociation on either prismatic or pyramidal planes. [37,38] Fig. 6-Slip and twinning systems in the a phase.…”
Section: B Deformation Modesmentioning
confidence: 99%